A LATTICE BOLTZMANN SIMULATION OF THE RHONE RIVER - PARMIGIANI, ANDREA; LATT, JONAS; BEGACEM, MOHAMED BEN; CHOPARD, BASTIEN (International journal of modern physics. C, Computational physics, physical computation, 2013)
We present a very detailed numerical simulation of the Rhone river in the Geneva area, using a Lattice Boltzmann (LB) modeling approach. The simulations of water ways are important to better predict and control their behavior when subject to exceptional event or new management strategies. Here, we investigate the current computing limits of using a three-dimensional (3D), free surface model to simulate a high resolution flow over a long section of the river, on a massively parallel computer. We argue that in a near future, computers will be powerful enough to tackle such a simulation. We also compare our results with a two-dimensional (2D) shallow water model to determine in which range a 3D free surface approach provides better insights. Finally, we discuss the advantage of a multi-scale approach for this type of problems.